ERBUK SEMANGGI SEBAGAI MINUMAN HERBAL - Saleh, Nini Jayanti; Soediro, Moses (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2017)
Innovation is needed to preserve local culinary clover as a culinary ingredient which becomes one of the elements of the tourist attraction. With the momentum of healthy lifestyle trend in Surabaya, a beverage product is createdfromlocal ingredients in Surabaya. A clover known in Latin asMarsilea Crenatais usually used as a Pecel Semanggi. Marsilea Crenata is knownasherbal medicine. It is usedto curesore throat, sprue, and fever. It contains high isoflavones.The herbal drinkis createdby producing clover powder through the stages of drying using dehydrator. The herbal beverage is produced through experimental stages with dry mix and crystallization method. Sensorytest is used to discover about the taste, aroma, color, and texture of the herbal drink. They are acceptable and 53.3% of panelists like it. Nutritiontest is conductedinBalai Riset dan Standardisasi Industri Surabayato discover the nutrition facts of the herbal drink. The herbal drink contains of 20,62% ash, 7,31% sugar, 1,16% protein, 6,15% carbohydrate, andenergy38,96 kcal/100 g.In further research other methodscan be usedsuch as vacuum drying or freeze drying so that the vitamin content is keep remain. The clover leaf utilization can be optimized by producing an instant herbal drink water clover. Thus the Kampung Semanggi as one of tourist destinations deserves to receive more attention, particularly fromthe government.